Gemination of a mandibular third molar: A rare case report - Arvind Venkatesh; Siddhartha Goel; Vijay Wadhwan; Vishal Bansal (Wolters Kluwer Medknow Publications, 2016)
The disturbances in the shape of the teeth include gemination, fusion, concrescence, dilaceration, talon cusp, dens in dente, dens evaginatus, taurodontism, and supernumerary roots. Gemination is defined as a single enlarged tooth or joined tooth in which the tooth count is normal when the anomalous tooth is counted as one, even though the exact pathogenesis may be questionable. Gemination is more common in the deciduous dentition compared to permanent dentition. This condition is rarely associated with mandibular third molars, and the terminology has often been a topic of debate when the condition in associated with this tooth. Here, we present a case of gemination associated with the mandibular third molar, showing an unusual and distinct crown and root morphology. The clinical and radiographic features, pulp chamber, and root canal morphology using stereomicroscopy and the histological features of the tooth have been discussed in detail.